A genome‐wide association study identifies a new variant associated with word reading fluency in Chinese children. (13th December 2022) - Wang, Zhengjun; Zhao, Shunan; Zhang, Liming; Yang, Qing; Cheng, Chen; Ding, Ning; Zhu, Zijian; Shu, Hua; Liu, Chunyu; Zhao, Jingjing
Abstract: Reading disability exhibited defects in different cognitive domains, including word reading fluency, word reading accuracy, phonological awareness, rapid automatized naming and morphological awareness. To identify the genetic basis of Chinese reading disability, we conducted a genome‐wide association study (GWAS) of the cognitive traits related to Chinese reading disability in 2284 unrelated Chinese children. Among the traits analyzed in the present GWAS, we detected one genome‐wide significant association ( p < 5 × 10 −8 ) on word reading fluency for one SNP on 4p16.2, within EVC genes (rs6446395, p = 7.33 × 10 −10 ). Rs6446395 also showed significant association with Chinese character reading accuracy ( p = 2.95 × 10 −4 ), phonological awareness ( p = 7.11 × 10 −3 ) and rapid automatized naming ( p = 4.71 × 10 −3 ), implying multiple effects of this variant. The eQTL data showed that rs6446395 affected EVC expression in the cerebellum. Gene‐based analyses identified a gene (PRDM10) to be associated with word reading fluency at the genome‐wide level. Our study discovered a new candidate susceptibility variant for reading ability and provided new insights into the genetics of developmental dyslexia in Chinese children. Abstract : A genome‐wide association study (GWAS) identified one genome‐wide significant variant rs6446395 (on 4p16.2 within EVC genes) associated with word reading fluency. Rs6446395 also showed significant association with Chinese character reading accuracy, phonological awareness and rapid automatized naming, implying multiple effects of this variant. Gene‐based analyses identified a gene (PRDM10) to be associated with word reading fluency at the genome‐wide level.